Left Behind?: Migration Stories of Two Women in Rural China - Fan, C. Cindy (Social Inclusion, 2020)
Women being left behind in the countryside by husbands who migrate to work has been a common phenomenon in China. On the other hand, over time, rural women’s participation in migration has increased precipitously, many doing so after their children are older, and those of a younger generation tend to start migrant work soon after finishing school. Although these women may no longer be left behind physically, their work, mobility, circularity, and frequency of return continue to be governed by deep-rooted gender ideology that defines their role primarily as caregivers. Through the biographical stories of two rural women in Anhui, this article shows that traditional gender norms persist across generations. Yingyue is of an older generation and provided care to her husband, children, and later grandchildren when she was left behind, when she participated in migration, and when she returned to her village. Shuang is 30 years younger and aspires to urban lifestyle such as living in apartments and using daycare for her young children. Yet, like Yingyue, Shuang’s priority is caregiving. Her decisions, which are in tandem with her parents-in-law, highlight how Chinese families stick together as a safety net. Her desire to earn wages, an activity much constrained by her caregiving responsibility to two young children, illustrates a strong connection between income-generation ability and identity among women of the younger generation. These two stories underscore the importance of examining how women are left behind not only physically but in their access to opportunities such as education and income-generating activity.